2019
DOI: 10.1371/journal.pone.0216674
|View full text |Cite
|
Sign up to set email alerts
|

Splice donor site sgRNAs enhance CRISPR/Cas9-mediated knockout efficiency

Abstract: CRISPR/Cas9 allows the generation of knockout cell lines and null zygotes by inducing site-specific double-stranded breaks. In most cases the DSB is repaired by non-homologous end joining, resulting in small nucleotide insertions or deletions that can be used to construct knockout alleles. However, these mutations do not produce the desired null result in all cases, but instead generate a similar, functionally active protein. This effect could limit the therapeutic efficiency of gene therapy strategies based o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…SkipGuide is evaluated on gRNAs that lead to DNA double-stranded breaks in a small window (6-bp) surrounding and including the AG splice site acceptor motif. End-joining repair at cut sites outside of this region [34][35][36][37], and ablations of an exon's splice donor sequence [37,38], have been shown to also lead to exon skipping. Hence, modelling these cases can be future extensions to SkipGuide.…”
Section: Discussionmentioning
confidence: 99%
“…SkipGuide is evaluated on gRNAs that lead to DNA double-stranded breaks in a small window (6-bp) surrounding and including the AG splice site acceptor motif. End-joining repair at cut sites outside of this region [34][35][36][37], and ablations of an exon's splice donor sequence [37,38], have been shown to also lead to exon skipping. Hence, modelling these cases can be future extensions to SkipGuide.…”
Section: Discussionmentioning
confidence: 99%
“…However, García-Tuñón et al , in their other research article on CRISPR, published recently, highlighted the limitation of CRISPR/Cas9 in effectively knocking out target DNA without a null variation inducing homology directed repair template in the construct. They went on to demonstrate that effective knockdown could be achieved if sgRNAs target the splice donor site of the gene 31 . Moreover, it has been shown that in CML, using a DNA targeting CRISPR would mean designing custom guide RNAs per patient as the breakpoints might differ per case at the DNA level 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last five years, the number of scientific papers reporting work on CRISPR/Cas9 in the context of leukemia research has increased enormously [ 84 , 93 , 94 , 95 , 96 ]. Many of them concern in vitro studies to clarify the role of a variety of genes in leukemia development [ 97 ].…”
Section: Crispr Gene Therapy In CMLmentioning
confidence: 99%